Delay discounting predicts COVID-19 vaccine booster willingness - Julia G. Halilova; Samuel Fynes‑Clinton; Caitlin M. Terao; Donna Rose Addis; R. Shayna Rosenbaum (Cognitive Research)
Abstract Developing ways to predict and encourage vaccine booster uptake are necessary for durable immunity responses. In a multi-nation sample, recruited in June–August 2021, we assessed delay discounting (one’s tendency to choose smaller immediate rewards over larger future rewards), COVID-19 vaccination status, demographics, and distress level. Participants who reported being vaccinated were invited back one year later (n = 2547) to report their willingness to receive a booster dose, along with reasons for their decision. After controlling for demographic variables and distress level, a greater tendency to discount future rewards was associated with reduced willingness to receive a booster dose. Thematic coding revealed that the most common reason for booster willingness was protection against COVID-19, and for unwillingness was non-necessity. The results identify delay discounting as a behavioral predictor of booster willingness that may be used to inform tailored approaches to increase booster uptake (e.g., trust in science vs. vaccine mandates).